Hospitality law : managing legal issues in the hospitality industry - Barth, Stephen (Hoboken : Wiley, 2012)
"Written to help teach hospitality students what they need to know to manage a facility legally, safely, and securely"--
Includes index.
Glossary: p. 471-477
Keywords: Hotels -- Law and legislation -- United States; Hospitality industry -- Law and legislation -- United States